2023
DOI: 10.1002/oby.23758
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent insulinotropic polypeptide monoclonal antibodies prevent and treat obesity in wild‐type and hyperphagic mice

Abstract: Objective This study aimed to investigate whether a glucose‐dependent insulinotropic polypeptide (GIP) monoclonal antibody (mAb) will promote weight loss in wild‐type mice and to determine effects of this mAb in preventing weight gain in ob/ob mice. Methods Phosphate‐buffered saline (PBS) or GIP mAb was injected intraperitoneally to wild‐type mice fed a 60% high‐fat diet (HFD). After 12 weeks, mice that received PBS were divided into two groups and were fed a 37% HFD for 5 weeks; one group received PBS, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A number of studies have indicated that immunisation against GIP peptides, as a means to stimulate active endogenous antibody generation, is an efficacious method of improving obesity-diabetes in rodents [Fulurija et al 2008;Irwin et al 2009;Montgomery et al 2010;Wolfe et al 2023], although suitability of this approach in humans is yet to be determined. Indeed, given the various important physiological actions of GIP [Figure 1], it may be anticipated that side-effects could occur with this approach.…”
Section: Gipr Immune-neutralisationmentioning
confidence: 99%
“…A number of studies have indicated that immunisation against GIP peptides, as a means to stimulate active endogenous antibody generation, is an efficacious method of improving obesity-diabetes in rodents [Fulurija et al 2008;Irwin et al 2009;Montgomery et al 2010;Wolfe et al 2023], although suitability of this approach in humans is yet to be determined. Indeed, given the various important physiological actions of GIP [Figure 1], it may be anticipated that side-effects could occur with this approach.…”
Section: Gipr Immune-neutralisationmentioning
confidence: 99%